A novel suture retention test for scaffold strength characterization in ophthalmology. - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2016)
Sutures are a common way to attach scaffolds in patients. For tubular cardiac scaffolds, the 'suture retention strength' is commonly used to evaluate the resistance of a scaffold against the pull-out of a suture. In order to make this quantity accessible for ophthalmological scaffolds the test procedure has been modified in a novel way. Polycaprolactone (PCL) films of different thicknesses and an amniotic membrane (AM) were used for the experiments. Circular samples with a radius of 7mm were taken and a suture was passed through each sample and tied to a loop. The sample was clamped in a tensile tester and a bolt was passed through the loop. The suture was then pulled with a constant deformation rate until pull-out occurred. The suture retention strength, the deformation at the suture retention strength, and the deformation at rupture were determined for each sample. The presented modified suture retention test allows to measure the relevant parameters of samples on the scale of ophthalmological scaffolds in a reproducible way. A comparison between the first data on PCL and AM has been made.